2008
DOI: 10.1007/s12229-008-9024-6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, Species Richness, and Ecological Specialization in Cyperaceae Tribe Cariceae

Abstract: Cyperaceae tribe Cariceae is characterized by both species richness and habitat diversity, making it an ideal system to study ecological specialization and niche differentiation. We present a phylogenetic hypothesis for the tribe based on nuclear and chloroplast DNA sequence comparisons (ETS-1f, ITS, trnL intron, trnL-trnF intergenic spacer) for 140 representative species from five continents, and use this hypothesis to suggest patterns of both niche conservatism and niche differentiation, particularly within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
105
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 32 publications
13
105
0
Order By: Relevance
“…Phylogenetic work has shown that this broader circumscribed Carex comprises three strongly supported clades (Siderostictae, Vignea, and Core Carex) and a weak to moderately supported clade, the Caricoid clade, which includes most unispicate and a few multispicate Carex species as well as the remaining genera traditionally considered within the tribe (Cymophyllus, Kobresia, Schoenoxiphium, and Uncinia; Starr et al 1999;Yen and Olmstead 2000;Roalson et al 2001;Waterway and Starr 2007;Waterway et al 2009). Within the Caricoid clade, two well-supported lineages are found: the Schoenoxiphium clade, including the former genus Schoenoxiphium plus two small clades of Carex species (one containing sections Junciformes and Aciculares and the other grouping C. distachya and allies; Gehrke et al 2010;Global Carex Group 2016), and another comprising the polyphyletic genus Kobresia, the monophyletic genus Uncinia, and several clades with mostly unispicate Carex species (Waterway et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic work has shown that this broader circumscribed Carex comprises three strongly supported clades (Siderostictae, Vignea, and Core Carex) and a weak to moderately supported clade, the Caricoid clade, which includes most unispicate and a few multispicate Carex species as well as the remaining genera traditionally considered within the tribe (Cymophyllus, Kobresia, Schoenoxiphium, and Uncinia; Starr et al 1999;Yen and Olmstead 2000;Roalson et al 2001;Waterway and Starr 2007;Waterway et al 2009). Within the Caricoid clade, two well-supported lineages are found: the Schoenoxiphium clade, including the former genus Schoenoxiphium plus two small clades of Carex species (one containing sections Junciformes and Aciculares and the other grouping C. distachya and allies; Gehrke et al 2010;Global Carex Group 2016), and another comprising the polyphyletic genus Kobresia, the monophyletic genus Uncinia, and several clades with mostly unispicate Carex species (Waterway et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Gehrke et al (2010); Hipp et al (2006); KĂŒkenthal (1909); Reznicek (1990); Starr and Ford (2009);Starr et al (2004Starr et al ( , 2008; Waterway and Starr (2007); Waterway et al (2009).…”
Section: Map 59 Asplundia Vagans Occurrence In Venezuelamentioning
confidence: 99%
“…Although molecular data (Starr et al, 2004(Starr et al, , 2008Waterway et al, 2009;Gehrke et al, 2010) resolve Uncinia as monophyletic, it is embedded in the very large genus Carex and is a major element in a core unispicate clade (Waterway and Starr, 2007;Starr and Ford, 2009) that also includes Cymophyllus and unispiculate species of Kobresia and Carex. Sister to this core unispicate clade is the Schoenoxiphium clade composed of Schoenoxiphium Nees and species of Carex.…”
Section: Uncinia Persmentioning
confidence: 99%
“…Psyllophora (Degland 1828:285). This classification was widely followed by most authors (Koyama 1962;Reznicek 1990;Dai 2000Dai , 2010Waterway et al 2007Waterway et al , 2009.…”
Section: Introductionmentioning
confidence: 99%